Influence of Melatonin on Cerebrovascular Proinflammatory Mediators Expression and Oxidative Stress Following Subarachnoid Hemorrhage in Rabbits. (11th February 2010) - Fang, Qi; Chen, Gang; Zhu, Weiwei; Dong, Wanli; Wang, Zhong
Abstract : The aim of this study is to analyze whether melatonin administration influenced the nuclear factor-kappa B (NF-κ B) activity, proinflammatory cytokines expression, and oxidative response in the basilar artery after SAH. A total of 48 rabbits were randomly divided into four groups: control group, SAH group, SAH + vehicle group, and SAH + melatonin group. All SAH animals were subjected to injection of autologous blood into cisterna magna twice on day 0 and day 2. The melatonin was administered intraperitoneally at a dose of 5 mg/kg/12 h simultaneously with SAH from day 0 to day 5. The basilar arteries were extracted on day 5 after SAH. As a result, we found that vascular inflammation and oxidative stress were induced in all SAH animals. In animals given melatonin, basilar arterial NF-κ B and pro-inflammatory cytokines were decreased in comparison to vehicle-treated animals. Measures of oxidative stress also showed significant downregulation after melatonin treatment. Furthermore, administration of melatonin prevented vasospasm on day 5 following SAH. In conclusion, post-SAH melatonin administration may attenuate inflammatory response and oxidative stress in the spasmodic artery, and this may be one mechanism involved in the therapeutic effect of melatonin on the subsequent vasospasm after SAH.